Explanatory exclusion and mental explanation. (2nd April 2016) - Moore, Dwayne
Abstract: Jaegwon Kim once refrained from excluding distinct mental causes of effects that depend upon the sufficient physical cause of the effect (Kim, 1984 ). At that time, Kim also refrained from excluding distinct mental explanations of effects that depend upon complete physical explanations of the effect (Kim, 1988, 1989 ). More recently, he has excluded distinct mental causes of effects that depend upon the sufficient cause of the effect, since the physical cause is individually sufficient for the effect (Kim, 2005 ). But there has been, to this point, no parallel shift in the explanatory realm, such that distinct mental explanations of effects that depend upon complete physical explanations of the effect are excluded since the physical explanation is objectively complete. In this paper I consider, defend, and apply this update to the principle of explanatory exclusion—an update, which, in the final analysis, demonstrates a significant advantage that non-reductive physicalism has over reductive physicalism.